An Analysis of the Management and Leadership Roles of Nurses Relative to the Health Insurance Portability and Accountability Act. Issue 1 (January 2015) - Kiel, Joan M.
<x xml:space="preserve">Abstract</x> Nurses have a great deal of interaction with patients. Given this, nurses play a vital role in conveying to patients knowledge of their privacy, security, and confidentiality of patient health information rights under the Health Insurance Portability and Accountability Act (HIPAA). Nurses also can be "at the head of the table" in their own organization and professional organizations in regard to facilitating the implementation of the HIPAA and making access to patient information more "consumer friendly." This article discusses the role that nurses can develop into concerning HIPAA implementation in an ever-burgeoning arena of consumer advocacy and consumer information.